BUDIDAYA DAN ANALISIS USAHATANI PISANG BARANGAN DI KABUPATEN DELI SERDANG SUMATERA UTARA - Sortha Simatupang; Besman Napitupulu; M Prama Yufdi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
Cultivation and Analysis of Barangan Banana Farm Operations in Deli Serdang Regency North Sumatra. Red Barangan banana is one of the cultivar kinds mostly cultivated in Deli Serdang, North Sumatra. The aim of this study was to obtain the characteristics of barangan banana cultivation technology and to analyze the banana farm operations. This is necessary as an evaluation for an improvement in order to increase the income of Barangan banana farmers in Deli Serdang. The research was conducted in two villages namely Talun Kenas and Siguci, STM Hilir Sub-district, Deli Serdang, North Sumatra Province from April to June 2008 by using a survey method and direct observation at the banana area. The primary data were collected by interviewing farmers managing the banana plants, while the secondary data were collected from related institutions. The results show that the farmers have sufficiently been efficient in managing the agricultural land by implementing multi-cropping. However, the technology for banana cultivation still needs improvement by optimizing the use of organic and inorganic fertilizers, plant maintenance, especially in the provision of healthy Barangan banana seeds. Barangan banana farming system provides profit with a B/C 1.1.Key words: Musa paradisiaca, characteristic, technology and farming systemABSTRAKPisang Barangan Merah adalah salah satu jenis kultivar yang paling banyak dibudidayakan di Deli Serdang Sumatera Utara. Tujuan pengkajian ini yaitu untuk mendapatkan karakteristik teknologi budidaya pisang barangan dan analisis usahatani tdari pisang tersebut. Pengkajian ini dilaksanakan di Desa Talun Kenas dan Siguci Kecamatan STM Hilir Kabupaten Deli Serdang, Provinsi Sumatera Utara dimulai April sampai Juni 2008 dengan metode survei dan pengamatan langsung ke lahan Pisang. Data primer diperoleh melalui wawancara dengan petani yang mengusahakan tanaman pisang. Data sekunder diperoleh dari lembaga terkait. Hasil pengkajian menunjukan bahwa petani telah cukup efien dalam mengkelola lahan pertanian dengan menanam tanaman lain secara tumpangsari. Teknologi budidaya tanaman pisang, masih memerlukan perbaikan dengan mengoptimalkan penggunaan pupuk organik, pupuk anorganik, perawatan tanaman, serta yang terutama ialah penyediaan bibit sehat pisang barangan. Usahatani pisang barangan memberikan keuntungan dengan nilai B/C 1,1Kata kunci : Musa paradisiaca , Karakteristik, teknologi, petani, sistem Usahatani